ANALYSIS OF FACTORS AFFECTING FEMALE UNEMPLOYMENT IN REGENCIES/CITIES IN BALI PROVINCE - Ni Luh Komang Santhi Purnama Sari; Putu Ayu Pramitha Purwanti (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Female unemployment is a critical issue in the context of economic and social development in Bali Province, especially due to the significant role of women in the informal and tourism sectors. This study aims to analyze the effects of education, age, regional minimum wage, and inflation on female unemployment rates in the nine regencies/cities of Bali Province during the 2014–2023 period. The method used is panel data regression analysis, employing the Common Effect Model (CEM) selected based on Chow and Lagrange Multiplier test results. The findings show that, simultaneously, all four independent variables significantly influence female unemployment. Partially, education and age have a negative and significant effect, the regional minimum wage has a positive and significant effect, and inflation has a positive but not significant effect. These results indicate that increasing age and controlling inflation can reduce female unemployment, while wage policies must be carefully evaluated to avoid hindering female labor absorption. This research is expected to provide valuable input for local governments in formulating more inclusive and gender-responsive employment policies in Bali.